Human Resource Management and Transformational Leadership: Strategies for Improving Innovation Behavior in MSMEs in West Sumatra with Organizational Culture as a Mediating Variable - Rio Nardo; Budi Santoso; Muhammad Ifan Fadillah (Yayasan Edukasi Cakrawala Nusantara, 2025)
This study aims to analyze the effect of human resource management and transformational leadership on innovation behavior in MSMEs in West Sumatra with organizational culture as a mediating variable. The research was conducted by taking a sample of 400 respondents who are MSMEs in West Sumatra. The data collection tool used was a questionnaire. The data obtained was processed with the SEM PLS (Structure Equation Modeling Partial Least Square) analysis technique using the SmartPLS 3.0 program. The results of this study explain that there is a positive and significant effect of HR Management variables on innovative behavior, there is a positive and significant effect of transformational leadership variables on innovative behavior, there is a positive and significant effect of HR Management variables on organizational culture, there is a positive and significant effect of transformational leadership variables on organizational culture, there is a positive and significant effect of organizational culture variables on innovative behavior, there is a positive and significant effect of HR Management on innovative behavior through organizational culture and there is a positive and significant effect of transformational leadership on innovative behavior through organizational culture.